Once a rebel - Putney, Mary Jo (Putney, Mary Jo. Rogues redeemed., 2017)
As Washington burns, Callista Brooke is trapped in the battle between her native England and her adopted homeland. She is on the verge of losing everything, including her life, when a handsome Englishman cuts through the violent crowd to claim that she is his. Callie falls into her protector's arms, recognizing that he is no stranger, but the boy she'd once loved, a lifetime ago. Lord George Gordon Audley had been Callie's best friend, and it was to Gordon she turned in desperation to avoid a loathsome arranged marriage. But the repercussions of his gallant attempt to rescue her sent Callie packing to Jamaica, and Gordon on a one way trip to the penal colony of Australia. Against all odds, Gordon survived. Finding Callie is like reclaiming his tarnished soul, and once again he vows to do whatever is necessary to protect her and those she loves. But the innocent friendship they shared as children has become a dangerous passion that may save or destroy them when they challenge the aristocratic society that exiled them both.